The case of the loose-toothed shark - Krulik, Nancy E. (Jack gets a clue, 2012)
Jack and his brainiac detective partner Elizabeth must work to clear Jack's name after he is accused of stealing a giant shark tooth fossil during his little sister Mia's birthday party at the aquarium.